Elimination of quantifiers and undecidability in spatial logics for concurrency - Caires, Luís (2019)
We thank Hongseok Yang for the illuminating discussion that prompted our counterexample in Section 4. We acknowledge Luís Monteiro, Daniel Hirschkoff and Davide Sangiorgi for all the rich exchanges and encouragement; and Luca Cardelli for many related discussions. E. Jeandel provided some references about quantifier elimination. This collaboration was supported by FET IST 2001-33310 Profundis. E. Lozes was also funded by an “Eurodoc” grant from Région Rhône Alpes.